A Contribution to the Modelling of Dynamic Problems for Periodic Plates - J. Jędrysiak (Engineering Transactions, 2015)
A certain problem of vibrations analysis of thin periodic plates is presented in this paper. The applied model describes the effect of the periodicity cell size on the overall plate behaviour. In the modelling procedure we use a concept of functions which describe oscillations inside the periodicity cell and have to be properly chosen approximations of solutions to eigenvalue problems for natural vibrations of a separated periodicity cell with periodic boundary conditions. In this paper we will show that for certain cases of that cell, an approximate form of those functions can be used.